ANALISIS INVESTASI, PAD DAN JUMLAH UNIT UKM TERHADAP PENYERAPAN TENAGA KERJA UKM DI KABUPATEN LABUHANBATU - Zulkarnain Nasution (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2018)
The purpose of this study is to analyze the effect of investment, PAD, the number of SMEs and the absorption of SMEs workforce in Labuhanbatu District. The sample was obtained from the statistics book of small and medium enterprises of Cooperative and SME Office 2007- 2016. The analytical method in this study is Ordinary Least Square (OLS) with the help of IBM SPSS 20 computer program. The result of analysis shows that SME investment and the number of SME business unit have a significant effect on the absorption of small and medium enterprises. Meanwhile, PAD has not significant effect on the absorption of small and medium enterprises